(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Public policy (PP) doctrine, being a substantial concept in many jurisdictions, is also among the evasive concepts given the contrary to practical application in the case law and complicated literature that is argued before many judges at different multinational levels. As a notion, PP has a vital impact on the execution of ICA awards in many adaptable ways.